Digital Marketing : Trends and Developments. - Gowpall, Y.; ProQuest (firma) (Cape Town : Juta & Company, Limited, 2024)
The book begins with outlining the Evolution of Digital Marketing. The proceeding chapters zone into the specific Mediums of Digital Marketing. The book then focuses on the Current Trends in Digital Marketing, Digital Marketing Strategies and Best Practices, Emerging Technologies and Innovations in Digital Marketing. Lastly, the final chapter of the book considers the ever-changing world of digital marketing by looking at Ethical Considerations in Digital Marketing.
5.8.2.2 Email marketing automation.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2025. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books